Prevalence and antimicrobial susceptibility profile of bacteria isolated from the hands of housemaids in Jimma City, Ethiopia - Ango, Tadele Shiwito; Gelaw, Negalgn Byadgie; Zegene, Girma Mamo; Teshome, Tizita; Getahun, Tesfalem (Frontiers in Public Health, 2024)
Introduction Bacterial pathogens continue to be a major cause of foodborne gastroenteritis in humans and remain a public health problem. Housemaids operating inside a kitchen could be the source of infection and may transmit disease-inflicting pathogens through contaminated hands. Objective This study aimed to assess the prevalence and antimicrobial susceptibility profile of bacteria isolated from the hands of housemaids in Jimma City, Ethiopia. Methods A laboratory-based cross-sectional study was employed among 234 housemaids. Hand swab samples from the dominant hand of the study participants were collected under sterile conditions following standard operating procedures. Then, in the laboratory, the swabs were inoculated aseptically using streak-plating methods on the growth media, such as mannitol salt agar [Staphylococcus aureus and coagulase-negative staphylococci], MacConkey agar [Klebsiella species and Proteus species], salmonella-shigella agar [Salmonella species and Shigella species], and eosin methylene blue agar [Escherichia coli (E. coli)]. In addition, a set of biochemical tests was applied to examine bacterial species. Data were double-entered into EpiData version 3.1 and then exported to the Statistical Package for Social Science (SPSS) version 26 for further analysis. Descriptive analyses were summarized using frequency and percentage. Results The proportion of housemaids’ hands containing one or more positive bacterial isolates was 72% (95% CI: 66.2, 77.8). The dominant bacterial isolates were Staphylococcus aureus (31.6%), Escherichia coli (21.3%), Salmonella species (1.3%), Shigella species (6.7%), Klebsiella species (23.1%) and Proteus species (14.7%). Fingernail status (AOR =15.31, 95% CI: 10.372, 22.595) and the removal of a watch, ring, and bracelet during hand washing (AOR = 20.844, 95% CI: 2.190, 9.842) were significantly associated with the prevalence of bacterial isolation. Most Staphylococcus aureus isolates were susceptible to chloramphenicol (98.6%). Escherichia coli isolates were susceptible to tetracycline (75%), ceftriaxone (79.2%), chloramphenicol (87.5%), and ceftazidime (77.1%). Eighty percent of isolated Shigella species were susceptible to chloramphenicol and gentamicin respectively. In addition, Klebsiella and Proteus species exhibited high susceptibility to chloramphenicol. However, their isolates showed resistance against a number of the tested antimicrobials. Staphylococcus aureus isolates (28.2%) were resistance to tetracycline. Moreover, One-quarter of Escherichia coli isolates were resistance to tetracycline, ceftriaxone, chloramphenicol, and ceftazidime. Whereas 46.7% and 48.5% of isolated Shigella species and Proteus species were resistance to tetracycline and ceftriaxone. Conclusion The hands of housemaids are important potential sources of pathogenic bacteria that would result in the potential risk of foodborne diseases. Most bacteria isolates were resistant to tetracycline, ceftriaxone, and ceftazidime. Therefore, practicing good hand hygiene helps to prevent and control the spread of antimicrobial-resistant microbes.